Mental health in Gaza: addressing sustainability challenges of ongoing war conflict - Mohammed Qutishat (Middle East Current Psychiatry)
Abstract Background The ongoing conflict in the Gaza Strip has severely impacted mental health sustainability due to the destruction of healthcare services, exacerbating issues like PTSD, anxiety, and depression. Access to psychological care is compromised, complicating recovery amid pervasive fear and community disruption. This review highlights the need for effective interventions and support strategies to enhance psychological rehabilitation in post-conflict settings. Method This systematic review, adhering to established guidelines, explored barriers to mental health rehabilitation in the Gaza Strip through literature searches in six databases using specific keywords. It included English-language studies from October 2023 to August 2024, focusing solely on challenges faced by individuals seeking mental health services in Gaza. Data extraction and quality appraisal utilized standardized tools, culminating in a narrative synthesis that identifies implications for future interventions. Results The analysis examines multiple studies on the challenges of sustaining mental health services in Gaza amid ongoing conflict, which include one qualitative, two quantitative, six systematic reviews, and one mixed-methods study. Critical barriers include infrastructure damage, restricted service access, a shortage of trained professionals, and economic struggles. These challenges highlight the urgent need for specialized mental health approaches that are tailored to Gaza’s unique socio-political context. Conclusion The Gaza conflict has severely impacted mental health services, highlighting the need for sustainable support systems. Implementing long-term strategies that build community resilience and train local professionals is essential. A sustainable approach to mental health, integrated with broader humanitarian efforts, is crucial for recovery and well-being.